Evolution - Futuyma, Douglas J.; Chase, Mark W; Endress, Peter K; Futuyma, Douglas J. (Sunderland, Sinauer Ass, 2013)
Thoroughly updated with new content, figures and citations, the third edition addresses major themes in contemporary evolutionary biology - including the history of evolution, evolutionary processes, adaptation, and evolution as an explanatory framework - at levels of biological organization ranging from genomes to ecological communities.
Glossary G 1-G14p.; Index I 1-I36p.
Keywords: Evolutionary biology; Evolutionary science; Genetic drift and variation; Anthropology